Penerapan Model Investigasi Kelompok terhadap Peningkatkan Pembelajaran Menulis Teks Berita Siswa Kelas VIII SMPN 12 Sigi - Kairupan, Juliana (Bahasantodea, 2016)
Based on the background of this research, The problem of the study are formulated in the following questions “what is the implementation of a group investigation model can improve learning writing news text of eight grade students at SMPN 12 Sigi and How is the improvement of ability by using group investigation model to the learning writing news text of eight grade students at SMP N 12 Sigi ? this research aimed to describe the implementation of group investigation model to the larning writing text of eight grade students at SMPN 12 Sigi and for describing the improvement of ability by using writing news text investigation model of ninth grade students at SMPN 12 Sigi. The kind of this research is clasroom action research that implemented with a cycle. Each of cycle, there are 4 (four) steps research, 1). Planning steps, 2). Action, 3). Observing, and 4). Reflection. The research result found that the assesment of the news element completeness aspect at the cycle I ( 31,81% ) and cycle II (77,27%). The presentation of appropriateness aspect at the cycle I (68,18%) and cycle II (100%). The Using of sentence aspect at the cycle I (77,27%) and cycle II (77,27%). The using of vocabulary aspect at the cycle I (63,63%) and cycle II (100%). The interesting of topic aspect at the cycle I (72,72%) and cycle II (90%). The using of accuracy spelling aspect at the cycle I (68,18%) and cycle II (100%). At the cycle I the completeness percentage achieving only (31,81%) and cycle II occur the improvement become (77,27%). The sixth aspect happen improvement from cycle I to cycle II. At the cycle I the average completeness percentage (7,4) and cycle II occur the imrovement and the completeness average percentage become (8,6).